2018
DOI: 10.19026/ajfst.14.5843
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proximate Composition and Sensory Attributes of Dark Chocolate Fortified with Wheat Germ

Abstract: The aim of this study is to characterize Dark Chocolate (DC) fortified with the Wheat Germ (WG) and to study the effect of standard storage for two months on sensorial properties. Preliminary studies showed that the best combination of WG is 10%. Proximate analysis showed that protein and total minerals contents of dark chocolate significantly (p0.05) increased by the addition of WG, whereas fat content significantly (p0.05) decreased, moisture and total carbohydrates were (p0.05) similar. As a result total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Wheat germ is a byproduct of the wheat milling industry and is characterized by high levels of protein, dietary fiber, essential amino acids, unsaturated fatty acids, and high polyphenol and flavonoid content. Al-Marazeeq (2018) fortified the dark chocolate with wheat germ (10%) and found that protein and mineral content increased significantly whereas the fat content decreased. The sensory properties of the fortified chocolate were moderate compared to the control.…”
Section: Recent Developments In Fortification Of Chocolatementioning
confidence: 99%
“…Wheat germ is a byproduct of the wheat milling industry and is characterized by high levels of protein, dietary fiber, essential amino acids, unsaturated fatty acids, and high polyphenol and flavonoid content. Al-Marazeeq (2018) fortified the dark chocolate with wheat germ (10%) and found that protein and mineral content increased significantly whereas the fat content decreased. The sensory properties of the fortified chocolate were moderate compared to the control.…”
Section: Recent Developments In Fortification Of Chocolatementioning
confidence: 99%
“…Physical, microbiological, and sensory properties were checked. Marazeeq (2018) D-tagatose and inulin Production of fortified dark chocolate by using D-tagatose and inulin to reduce overall calorie content and glycemic index. Fortifying agents were added in the powder form and then the physiochemical properties were checked.…”
Section: Approaches To Fortify Dark Chocolatementioning
confidence: 99%
“…Two months of controlled storage did not affect the sensory properties of the chocolate. So, it can be claimed fortification provided a healthier option for all age groups people ( Marazeeq, 2018 ).…”
Section: Approaches To Fortify Dark Chocolatementioning
confidence: 99%
See 1 more Smart Citation